2020
DOI: 10.1111/1748-5967.12468
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification and expression analyses of Defensin genes in the mealworm beetle Tenebrio molitor

Abstract: Defensins are a major family of antimicrobial peptides that serve as the innate immune defense of both vertebrates and invertebrates. Due to their antimicrobial, chemotactic, and regulatory activities, Defensins have been exploited for their therapeutic potential. Insect Defensins are cysteine-rich and contain an N-terminal loop, α-helix, and antiparallel β-sheet, forming a "cysteine-stabilized alpha beta (CSαβ)" or "loop-helix-sheet" structure. In this study, we identified the full-length open reading frame (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Consistent with previous findings, the decreased survival rates of TmToll-3 -silenced T. molitor larvae following E. coli infection observed herein suggested that humoral innate immunity could occur via TmToll-3 . TmToll3 silencing in larvae rendered larvae more susceptible to E. coli infection and suppressed certain AMP genes induced by E. coli challenge, including TmTenesin-1, -4, TmDefensin, TmDefensin-like, TmColeoptericin-A, -B, -C , and TmAttacin-1a, -1b, -2 , all four of which belong to AMP families known to exhibit antibacterial activity against Gram-negative bacteria [ 49 , 50 , 51 , 52 ]. Tm Toll-7 and Tm Toll-2 have been reported to activate their downstream NF-kB transcription factor, which leads to the induction of immune response genes including AMP genes [ 30 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings, the decreased survival rates of TmToll-3 -silenced T. molitor larvae following E. coli infection observed herein suggested that humoral innate immunity could occur via TmToll-3 . TmToll3 silencing in larvae rendered larvae more susceptible to E. coli infection and suppressed certain AMP genes induced by E. coli challenge, including TmTenesin-1, -4, TmDefensin, TmDefensin-like, TmColeoptericin-A, -B, -C , and TmAttacin-1a, -1b, -2 , all four of which belong to AMP families known to exhibit antibacterial activity against Gram-negative bacteria [ 49 , 50 , 51 , 52 ]. Tm Toll-7 and Tm Toll-2 have been reported to activate their downstream NF-kB transcription factor, which leads to the induction of immune response genes including AMP genes [ 30 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression patterns of 14 AMP genes including TmTenecin1, 2, 3 , and 4 ( TmTene1 , − 2 , − 3 , and − 4 ) ( Kim et al, 1998 ; Chae et al, 2012 ; Yang et al, 2017 ), TmDefensin and TmDefensin-like ( TmDef and TmDef-like ) ( Jang et al, 2020b ), TmColeoptericin-A and -B ( TmColeA and − B ) ( Zhu et al, 2014 ; Jang et al, 2020a ), TmAttacin-1a, −1b and -2 ( TmAtt1a , − 1b and − 2 ) ( Jo et al, 2018 ), TmCecropin-2 ( TmCec2 ) ( Ali Mohammadie Kojour et al, 2021 ), and TmThaumatin - like protein-1 and − 2 ( TmTLP1 and − 2 ) ( Noh and Jo, 2016 ; Kim et al, 2017 ), were examined by qRT-PCR with the AMP gene-specific primers ( Table 1 ). A relative quantitative PCR was performed as detailed above in an AMP-specific primer.…”
Section: Methodsmentioning
confidence: 99%
“… Keshavarz et al. (2019) Jang et al. (2020b) Defensin 2 Full sequences not presented in references, Authors indicated defensins region: MPHEDVEVFEEAVHRVERGFFCNPGLCHRQCKQSGHRRASCSGDECVCLG The highest expression after E. coli immunization of larvae; the AMP gene expression observed in fat body, gut, and Malpighian tubules of young larvae.…”
Section: Insects In Poultry Nutritionmentioning
confidence: 99%
“… Keshavarz et al. (2019) Jang et al. (2020b) Thaumatin-like proteins 1 and 2 Immunized larvae of T. molitor with E. coli ATCC K12, S. aureus ATCC RN4220, C. albicans ATCC/the fat body, hemocytes, gut, and Malpighian tubule Thaumatin-like protein, GenBank (XP_012568089.2): MSDSCLMNIGGHQVTFYIHNKCPFPIWPATPSNTGQPIIAYGGFCLASSQTKKIQAPWSWSGRIWASTGCNFDSNSWKPS CETGDSDGKLACNGLIGTPP ATLDEITLQGDKGKTNFYGVSLVDGYIVPVSITPSKNINSKCNIEGCLKDVKSLCPNELQ SLESVKKKEEEEAKKKEVQL KAVKADGKSAEEVKDNGAIY Analysis of thaumatin-like-proteins 1 and 2 gene expression (qRT–PCR) and antimicrobial activity Antifungal activity, C. albicans The highest expression was observed in larvae infected with C. albicans.…”
Section: Insects In Poultry Nutritionmentioning
confidence: 99%